Vector magnetic field measurement based on magnetic fluid and high-order cladding-mode Bragg grating. (November 2021) - Zhang, Junying; Chen, Fengyi; Wang, Ruohui; Qiao, Xueguang; Chen, Haibin; Zhang, Xiongxing
Highlights: Both the fiber core and the fiber cladding comprise the Bragg grating inscriptions. The cladding modes can simultaneously sense the magnitude and direction of the magnetic field. The core mode can measure temperature, overcoming the temperature cross sensitivity issue of the FBG sensors. Abstract: An optical fiber-based vector magnetic field sensor combining fiber Bragg gratings (FBGs) and magnetic fluids (MFs) is proposed and experimentally demonstrated. The Bragg gratings are inscribed on the core and the cladding of a multi-clad fiber (MCF). Splicing the MCF with a standard single-mode fiber (SMF) via core mismatch provides a cladding-mode generation mechanism. Then, the high-order cladding mode is excited with the increasing off-axis distance. There are two kinds of resonant modes in the reflection spectrum of the sensor, which are the high-order cladding mode and the fundamental core mode. The intensity of the first mode shows an excellent response to the magnetic field intensity and the direction. The intensity sensitivity of the magnetic field sensor is −0.143 dB/Oe in a linear range of 60–110 Oe. Furthermore, the second mode intensity is quite stable and varies with the ambient temperature. Thus, the proposed magnetic field sensor can simultaneously measure the magnetic field and the temperature.